Object-Oriented Application Framework on Manufacturing Domain - Lee, Sai Peck; Thin, Siew Khim; Liu, Hong Song (Malaysian Journal of Computer Science, 2000)
The problematic issues in the development of manufacturing software systems are related to the various nature of manufacturing systems, which are wide, dynamic and complex. The purpose of this paper is to provide a solution by using framework-based software engineering to solve these problems. Framework-based software engineering is the idea of constructing software systems based on the integration of reusable components rather than developing software from scratch. The manufacturing application framework proposed in this paper is to be developed as a set of integrated reusable components, which can be adapted to suit specific manufacturing applications. This paper focuses on two subdomains of the manufacturing domain, i.e., Production Management (PM) and Statistical Quality Control (SQC). A generic model is defined based on the structure and behavior of each of the PM and SQC subdomains, from which the design infrastructure of the application framework is derived, based on the concept of design pattern. The details of the application framework development by integrating object-oriented technology and component-based development to achieve large-scale software reuse for manufacturing application develop-ment projects are also discussed.